Back to basics for the IPCC: applying lessons from AR6 to the Seventh Assessment Cycle - Slade, R.; Pathak, M.; Connors, S.; Tignor, M.; Okem, Andrew Emmanuel; Leprince-Ringuet, N. (Nature Portfolio, 2024)
The Intergovernmental Panel on Climate Change (IPCC) has been producing influential reports for over 35 years. As the IPCC’s Seventh Assessment Report (AR7) cycle begins, we offer our perspective as former members of the IPCC Technical Support Units from Working Groups I, II & III, and the Synthesis Report on lessons learned during the Sixth Assessment Report (AR6) cycle. We identify three broad issues that, if addressed, could reinforce and sustain the IPCC in continuing its mission to comprehensively assess the scientific understanding of human-induced climate change. These are the imperative to ensure balanced representation, the importance of author recognition, and the need for improved institutional memory. Our recommendations include addressing skill and training needs, tackling barriers to participation particularly for Global South authors, and ensuring all contributors receive appropriate recognition for their efforts. We focus, in particular, on feasible incremental changes that could be implemented during AR7 without major changes to the underlying procedures that require approval by the 195 member governments that make up the IPCC.